P‐116: The Investigation of Recovery Time of Ultraviolet Induced Multi‐domain Vertically Aligned (UV2A) LC Mode. Issue 1 (May 2016) - Li, Xiang; Hsieh, Chung-Ching; Zhao, Yong-Chao; Zhang, Yu; Zhao, Ren-Tang; Song, Yan-Jun; Ren, Wei; Yuan, Chun-Ge; Chiu, Chung-Yi; Lee, Chia-Yu
Abstract : The Ultraviolet induced multi‐domain Vertically Aligned (UV2A) liquid crystal mode has wide application for manufacturing large size LCD‐TV panel due to the high contrast ratio and fast response time. But the UV2A LCD mode has a main drawback that is slow recovery time for adapt to mass production. In this study, we have investigated the effect of dielectric constant, pre‐tilt, driving voltage and LC mode on the recovery time.